Consumer behavior towards discounted suboptimal foods in grocery stores among Gen Z and Millennial Filipinos - Sanchez, Geraldine Sofia R.; Pagulayan, Jin Mark DG. (Quezon City University of the Philippines Diliman, 2024)
The study aimed to assess the consumer behavior of Generation Z and Millennial Filipinos regarding price-reduced suboptimal foods (SF). Filipino consumers (n=385) aged 18-43 yrs old were surveyed about: (1) food purchasing habits, (2) grocery shopping behavior, (3) food waste behavior, (4) use of quality cues, and (5) quality perception of SF. Results showed that sociodemographic factors such as age group, level of education, and monthly household income influence (p<0.05) food purchasing habits. Gen Z and Millennial consumers were generally observed to make unplanned purchases. Value for money is prioritized by such consumers resulting in products being inspected more thoroughly and sale items to be more preferred. However, most of the respondents were skeptical over discounted SF (mean=3.06, neither agree or disagree). Despite this, little to nothing of uneaten food gets thrown away unless it was spoiled or expired, indicating that Gen Zs and Millennials were concerned about throwing away food (mean=4.04, agree). In addition, they want good quality food and evaluate quality through price, expiry, and appearance. With this, Generation Z and Millennial Filipinos have a low quality perception of SF (11.7% acceptance) that are visually, temporally, and peripherally deviated. Consequently, they have low purchase intent towards price-reduced SF. The PESTLE analysis highlights that the Philippine government, through the FDA and other agencies, enforces food safety and consumer protection laws, and promotes sustainability and food waste reduction. The demand for cheaper food options increased amid economic challenges, and digital marketing is important with the rise of e-commerce. Findings from this study could be used by food industry actors and policy makers in their efforts to reduce food waste due to the rejection of suboptimal foods.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Consumer behavior -- Philippines; Suboptimal foods